Perceptions and influences on the choice of private institutions of higher learning for further education - Zain, Osman M.; Ibrahim, Andy-Bachtiar; Anis, Azilah; Jan, Muhammad Tahir (2013)
There are more than 500 institutions of private higher education comprising of colleges, university colleges, and fully university status. These institutions are supposed to help fill the gap of limited seats for potential students in Government Institutions of Higher learning. A total sample of 375 students comprising student of year 11, 12, and 13 education levels were used in the study. These students are in the British equivalent O and A level of education. A questionnaire containing 46 statements were distributed randomly to the respondents during the motivation seminar at their respective schools. A factor analysis is performed on these statements producing results on the dimensions of influences and perceptions related to private institutions of higher education. The results of the study indicate that all the influencing factors that are supposed to determine the choice of Institution to further study is positively. These are the programme of the study at the institution, medium of instruction used, and the source of the information gathered from about the Institution. Three dimensions of perceptions on the Private Institutions of Higher Learning are also found to be related to the choice of the Institution to further study.